RANCANG BANGUN CONTROLLER MOTOR DC 36V PADA KENDARAAN LISTRIK NGEBUTS DALAM AJANG SHELL ECO-MARATHON ASIA PASIFIC AND THE MIDDLE EAST 2023 : RANCANG BANGUN CONTROLLER MOTOR DC 36V PADA KENDARAAN LISTRIK NGEBUTS DALAM AJANG SHELL ECO-MARATHON ASIA PASIFIC AND THE MIDDLE EAST 2023 - Hidayatullah, Muhammad; Ahmad Hasibuan, Thohar; Aulia, Masyitah (Hexagon Jurnal Teknik dan Sains, 2024)
Shell Eco-Marathon is an activity organized by the Shell company. This activity aims to increase the creativity and innovativeness of the participants in finding innovations in fuel use or fuel substitute innovations. Innovation in this activity can help realize the spirit of a future energy leader, change maker, perseverance, collaboration, innovation, and purpose to help create a cleaner future. NgebUTS is a Prototype Electric vehicle that is energy-efficient for the Shell Eco-Marathon, uses a Lithium Battery, and is driven by a DC motor. It is hoped that NgebUTS will become an innovative energy-saving vehicle ready to be used for the energy transition to renewable energy.